2014
DOI: 10.1016/j.diabet.2014.05.002
|View full text |Cite
|
Sign up to set email alerts
|

Perceived psychosocial stress and glucose intolerance among pregnant Hispanic women

Abstract: Aim Prior literature suggests a positive association between psychosocial stress and the risk of diabetes in non-pregnant populations, but studies during pregnancy are sparse. We evaluated the relationship between stress and glucose intolerance among 1115 Hispanic (predominantly Puerto Rican) prenatal care patients in Proyecto Buena Salud, a prospective cohort study in Western Massachusetts (2006–2011). Methods Cohen’s Perceived Stress Scale (PSS-14) was administered in early (mean = 12.3 weeks gestation; ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
27
1
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(33 citation statements)
references
References 35 publications
3
27
1
2
Order By: Relevance
“…A previous study by Silveira et al reported that an increase in stress level between early to mid-pregnancy substantially increased the odds of developing GDM among Hispanic women, compared to those with no change or a reduction in stress. [35] Although we were unable to assess the temporal relationship between stress during the early stage of pregnancy and the risk of developing GDM or excess/inadequate GWG, our study extended previous findings by suggesting that there may be associations between stress around the time of GDM diagnosis and increased risk of excess or inadequate total GWG. Second, although we did not observe mediating role of diet and physical activity, it is possible that the measures were not accurate, resulting in lack of observation.…”
Section: Discussionsupporting
confidence: 67%
“…A previous study by Silveira et al reported that an increase in stress level between early to mid-pregnancy substantially increased the odds of developing GDM among Hispanic women, compared to those with no change or a reduction in stress. [35] Although we were unable to assess the temporal relationship between stress during the early stage of pregnancy and the risk of developing GDM or excess/inadequate GWG, our study extended previous findings by suggesting that there may be associations between stress around the time of GDM diagnosis and increased risk of excess or inadequate total GWG. Second, although we did not observe mediating role of diet and physical activity, it is possible that the measures were not accurate, resulting in lack of observation.…”
Section: Discussionsupporting
confidence: 67%
“…Overall, 48 publications were included in this review (Figure 1, Table 1, Table 2, Table 3, Supplementary Table 1). Of these, 30 described prospective observational studies[20,21,23,24,26,27,29-31,34,35,37,38,41,43-45,47-49,51,54,57,58,60-62,65-67], 15 described retrospective observational studies[22,25,28,32,39,40,42,46,50,53,55,56,59,63,64], and three described randomized controlled trials (RCTs)[33,36,52], two of which reported only baseline data[36,52]. Two publications described the same study, but reported different subgroup analyses[23,29].…”
Section: Resultsmentioning
confidence: 99%
“…A total of 28 studies included only women with GDM[20,23,26-29,31,33,35-38,40,43-45,47-49,51-53,57,58,60,61,63,64], 14 included women with either GDM or pre-existing diabetes (although the type was not always reported)[22,25,39,41,42,46,50,54-56,59,62,65,66], one included women with either GDM or type 1 diabetes[34], one included only women with type 1 diabetes[67], one included only women with pre-existing diabetes (type not reported)[30] and three did not report the type of diabetes[21,24,32] (Tables 1-3, Supplementary Table 1). Sample sizes ranged from 36[65] to more than 32 million in a retrospective analysis of a nationwide hospital database[22] (Tables 1-3, Supplementary Table 1).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations